High diagnostic utility incorporating a targeted neurodegeneration gene panel with MRI brain diagnostic algorithms in patients with young-onset cognitive impairment with leukodystrophy - Chen, Zhiyong (2021)
Leukodystrophies are a diverse group of genetic disorders that selectively involve the white matter of the brain and are a frequent cause of young-onset cognitive impairment. Genetic diagnosis is challenging. Data on the utility of incorporating brain magnetic resonance imaging (MRI) diagnostic algorithms with next-generation sequencing (NGS) for diagnosis in a real-life clinical setting is limited. We performed sequencing using a custom-designed panel of 200 neurodegeneration-associated genes on 45 patients with young-onset cognitive impairment with leukodystrophy, and classified them based on van der Knaap et al.'s MRI diagnostic algorithm. We found that 20/45 (44.4%) patients carried pathogenic variants or novel variants predicted to be pathogenic (one in CSF1R, two in HTRA1 and 17 in NOTCH3). All patients with an established genetic diagnosis had an MRI brain pattern consistent with a specific genetic condition/s. More than half (19/37, 51.4%) of patients with MRI changes consistent with vascular cognitive impairment secondary to small vessel disease (VCI-SVD) had pathogenic variants, including all patients with pathogenic NOTCH3 (17/19, 89.5%) and HTRA1 variants (2/19, 11.5%). Amongst patients harboring pathogenic NOTCH3 variants, 13/17 (76.5%) carried the p.R544C variant seen predominantly in East Asians. Anterior temporal white matter involvement was seen only in patients with pathogenic NOTCH3 variants (6/17, 35.3%). Overall, we demonstrated a high diagnostic utility incorporating a targeted neurodegeneration gene panel and MRI-based diagnostic algorithms in young-onset cognitive impairment patients with leukodystrophy.